Borderline Personality Features and Mate Retention Behaviors: The Mediating Roles of Suspicious and Reactive Jealousy - Virgil Zeigler-Hill; Jennifer Vonk (Sexes, 2023)
We investigated the roles that suspicious jealousy and reactive jealousy might play in the associations between borderline personality features (BPF) and mate retention behaviors. Study 1 (N = 406) found that BPF had positive indirect associations with benefit-provisioning behaviors and cost-inflicting behaviors through suspicious jealousy but not through reactive jealousy. Study 2 (N = 334 (a dyadic sample of 167 romantic couples)) revealed actor effects such that BPF had positive indirect associations with benefit-provisioning behaviors and cost-inflicting behaviors through suspicious jealousy for both men and women. In addition, the positive association between BPF and benefit-provisioning behaviors was mediated by reactive jealousy in women but not in men. The only partner effect that emerged from these analyses showed that BPF in women were negatively associated with the benefit-provisioning behaviors reported by their male partners. Discussion focuses on the implications of these results for the function that jealousy might serve in the strategies used by individuals with BPF to maintain their romantic relationships.